Contributions to Knowledge of the Dictyocaulus Infection of the Red Deer - M. González-Velo; A. Espinosa-Sánchez; A. Ripa; M. A. Hurtado-Preciado; M. A. Habela Martínez-Estéllez; J. L. Fernández-García; C. Bazo-Pérez (Veterinary Sciences)
Dictyocaulosis is a parasitic disease that affects ungulate species, including red deer (Cervus elaphus). The genus Dictyocaulus comprises eighteen species, but only four have been reported to infect red deer. The disease is characterized by respiratory tract infection, particularly in the lungs, bronchi, and bronchioles, leading to inflammatory and hemorrhagic microscopic lesions, as well as emphysema and edema. The biological cycle involves a female ovipositing larvated eggs in the bronchi and trachea, which are expelled to the exterior through coughing or feces, releasing L1 into the environment. In this study, 106 adult red deer were collected from seven locations in Extremadura (Spain). Eight positive lungs were initially assessed by morphological identification, revealing a mean intensity of 13.3 adult worms per infected lung, with a global decrease to an average of 1.8 adult worms per sampled lung. The presence of adult worms in the upper and middle respiratory tract was confirmed through anatomopathological analysis. Molecular identification was performed by sequencing the COI gene. The results indicated the presence of three genetic groups, supported by significant subdivision using the ɸST measure. D. cervi and D. viviparus exhibited their respective matrilineal ancestry, while D. eckerti and D. cervi demonstrated matrilineal sharing. Consequently, the possibility of introgression between these two species was suggested. Although D. viviparus had previously been identified in the same Spanish region based on morphological characteristics, D. cervi and D. eckerti were reported for the first time in the explored geographic area.